Establishing a sense of home for the elderly a case study on the senior-care communities of Davao City - Reyes, Fraulein Anne Marie V.; Juanga, Jean Marie V. (2020)
Despite the imminent demographic shift in the country, the Philippines had not yet addressed its current issues regarding the aging population. Most senior-care communities focus only on the basic clinical requirements and neglect the at-homeness experience of its residents. For this reason, the study sought to determine a holistic and elderly-sensitive environment that establishes a ?sense of home? community experience and employs suitable residential care for the elderly. The theories by Rijnaard et al (2016), Molony et al (2007), and Glass & Skinner (2013) were mainly used to define the approach of the research. The study was conducted on 6 out of 9 senior-care communities in Davao City. It employed the case study research strategy and used both qualitative and quantitative methods. Results from the multiple linear regression analysis showed that all 15 factors identified by Rijnaard et al (2016) contributed to the ?sense of home? experience, with each factor differing in relative contribution. Further analysis also revealed that these factors are largely/strongly correlated to the quality of home. The needs and preferences of the elderly were greatly affected by their physical constraints. Based on the gathered data, the suitable type of residential care for the elderly of Davao City is a continuous care retirement community (CCRC). It transpired that a CCRC characterized by small-scale decentralized living units has the potential to establish a holistic and elderly-sensitive environment. It should possess the 15 factors influencing ?sense of home?. If not, at least have those with the most relative contribution. Seemingly, there is importance in having the community resemble a home, rather than an institution. In the hopes of pushing the Philippines? aging population to a better future, the outcome of this study was able to shed light on new methods in improving the elderly?s welfare and well-being.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020